Polyadenylated sequencing primers enable complete readability of PCR amplicons analyzed by dideoxynucleotide sequencing - Beránek, Martin; Drastíková, Monika; Petera, Jirí (Acta medica (Hradec Kralove), 2012)
Dideoxynucleotide DNA sequencing is one of the principal procedures in molecular biology. Loss of an initial part of nucleotides behind the 3' end of the sequencing primer limits the readability of sequenced amplicons. We present a method which extends the readability by using sequencing primers modified by polyadenylated tails attached to their 5' ends. Performing a polymerase chain reaction, we amplified eight amplicons of six human genes (AMELX, APOE, HFE, MBL2, SERPINA1 and TGFB1) ranging from 106 bp to 680 bp. Polyadenylation of the sequencing primers minimized the loss of bases in all amplicons. Complete sequences of shorter products (AMELX 106 bp, SERPINA1 121 bp, HFE 208 bp, APOE 244 bp, MBL2 317 bp) were obtained. In addition, in the case of TGFB1 products (366 bp, 432 bp, and 680 bp, respectively), the lengths of sequencing readings were significantly longer if adenylated primers were used. Thus, single strand dideoxynucleotide sequencing with adenylated primers enables complete or near complete readability of short PCR amplicons.
Keywords: Sequence Analysis, DNA; Nucleic Acid Amplification Techniques; techniky amplifikace nukleových kyselin; sekvenční analýza DNA; Humans; Polymerase Chain Reaction; DNA Primers; polymerázová řetězová reakce; Dideoxynucleotides; DNA primery; lidé; dideoxynukleotidy